You are on page 1of 2

f (5) = −3 A(5;−3) ‫

 ا‬C f( ) f (xA ) = yA ( )
A( x A ; y A ) ‫
 ا‬C f
(  ‫(      ) أو‬C ) a (  ‫(      ) أو‬C )
f ′(4) = −2 f ′( x 0 ) = a
f f

4 ‫ ! ا ذات ا‬− 2 x 0 ‫! ا ذات ا‬
f (− 8) = 7 ( )
2 (  ‫      ) أو‬C f f (xA ) = yA a (  ‫      ) أو‬C f ( )
f ′(− 8) = 2 ‫و‬ A(− 8;7 ) ‫! ا‬ f ′( x A ) = a ‫و‬ A( x A ; y A ) ‫! ا‬

f ′(5) = −1
( )
5 ‫    ! ا ذات ا‬C f
f ′( x 0 ) = a
x 0 ‫    ! ا ذات ا‬C f( )
y = − x + 1 ‫ ذو ا د‬#$% ‫ ازي ا‬ y = ax + b ‫ ذو ا د‬#$% ‫ ازي ا‬
f (− 4) = 3 ( )
A(− 4;3) ‫    ! ا‬C f f (xA ) = yA ( )
A( x A ; y A ) ‫    ! ا‬C f
f ′(− 4) = −6 ‫و‬ y = 2 − 6 x ‫ ذو ا د‬#$% ‫ ازي ا‬ f ′( x A ) = a ‫و‬ y = ax + b ‫ ذو ا د‬#$% ‫ ازي ا‬
f (1) = 7 , - ‫*ى أو‬+ )  !(  ‫ آ‬7  C f ( ) f ( x0 ) = a ( , - ‫*ى أو‬+ )  !(  ‫ آ‬a  C f ( )
f ′(1) = 0 ‫و‬ 1 ‫( ! ا ذات ا‬ f ′( x 0 ) = 0 ‫و‬ x 0 ‫أو ذروة ! ا ذات ا‬
f (1) = 4 f (xA ) = yA
f ′(1) = 0 ‫و‬
( )
‫روة‬1‫ آ‬A(1;4)  C f
f ′( x A ) = 0 ‫و‬
( )
‫روة‬1‫ آ‬A( x A ; y A )  C f

− 1 ‫(    ! ا ذات ا‬C ) x0 ‫(    ! ا ذات ا‬C )
f ′(− 1) = 0 f
f ′( x 0 ) = 0 f

. ‫ر اا‬2  ‫ازي‬ . ‫ر اا‬2  ‫ازي‬
( )
x = 1 ‫ ذو ا د‬#$% ‫  ا‬C f 4 lim f ( x ) = −∞
x →1
( )
x = a ‫ ذو ا د‬#$% ‫  ا‬C f 4 lim f ( x ) = ±∞
x →a
5‫*ا‬$‫ر ا‬2  ‫ رب ازي‬#$% ‫آ‬ 5‫*ا‬$‫ر ا‬2  ‫ رب ازي‬#$% ‫آ‬
( )
y = −4 ‫ ذو ا د‬#$% ‫  ا‬C f 4 lim f ( x ) = −4
x → +∞
( )
y = b ‫ ذو ا د‬#$% ‫  ا‬C f 4 lim f ( x ) = b
x → ±∞

(+ ∞ ) ‫ار‬78
‫ر اا‬2  ‫ رب ازي‬#$% ‫آ‬ (± ∞ ) ‫ار‬78‫ر اا‬2  ‫ رب ازي‬#$% ‫آ‬
‫*ع‬: ‫ رب ; أو‬#$% ‫  ود‬$2 4 lim f ( x ) = +∞ ‫*ع‬: ‫ رب ; أو‬#$% ‫  ود‬$2 4 lim f ( x ) = ±∞
x → −∞ x → ±∞

(− ∞ ) ‫ار‬78 <:= >? (± ∞ ) ‫ار‬78 <:= >?
‫ ذو‬#$% ‫(  ا‬C f ) 4 lim [ f ( x ) − (− 2 x + 1)] = 0 ‫ ذو ا د‬#$% ‫(  ا‬C f ) 4 lim [ f ( x ) − (ax + b )] = 0
x → −∞ x → ±∞

(− ∞ ) ‫ار‬78 ; ‫ رب‬#$% ‫ آ‬y = −2 x + 1 ‫ا د‬ (± ∞ ) ‫ار‬78 ; ‫ رب‬#$% ‫ آ‬y = ax + b
2x 2x
lim = 0  ! f ( x ) = −2 x − 5 + 2
2
x → ±∞ x + 2 x − 1 x + 2x − 1 ( )
 C f 4 lim g ( x ) = 0 @( f ( x ) = ax + b + g ( x )
x → ±∞
‫ رب‬#$% ‫ آ‬y = −2 x − 5 ‫ ذو ا د‬#$% ‫  ا‬C f ‫و‬( ) (± ∞ ) ‫ار‬78 ; ‫ رب‬#$% ‫آ‬ y = ax + b ‫ ذو ا د‬#$% ‫ا‬
(± ∞ ) ‫ار‬78 ;
DE‫* ا‬%$‫ا‬ ‫ق‬$BC‫ ا‬8?
( )
D G  ‫ا‬: D$‫   ت ! آ اط ا‬C f ℜ G D ‫ل‬7 , ‫ق‬$BC‫  ا‬f ‫ا!ا‬
f ( x ) − f (a )
l   a ‫(   س ! ا ذات ا‬C ) f a ! ‫ق‬$BI 8? ‫ دا‬f 4 lim = l ∈ℜ
x →a x−a
f ( x ) − f (a )
‫ر‬2  ‫ ازي‬a ‫  س ! ا ذات ا‬LME  C f ( ) x →a
lim
x−a
= ±∞
5‫*ا‬$‫ا‬ a ! ‫ق‬$BI 8? *K ‫ دا‬f 4
f ( x ) − f (a ) f ( x ) − f (a ) 
‫ر‬%‫ ا‬G a ‫  س ! ا ذات ا‬LME  C f ( ) l ≠ l ′ ، lim = l ′ ، lim =l
f
x → a x−a p
x → a x−a
G ‫ ا‬G a ‫  س ! ا ذات ا‬LME  ‫ و‬l ′  *K G=‫ و‬a ! ‫ر‬%‫ ا‬G‫ و‬G ‫ ا‬G ‫ق‬$BI 8? ‫ دا‬f 4
 ‫ زاو‬E a ‫ ا ذات ا‬, % . l 
a ! ‫ق‬$BI 8?
DE‫* ا‬%$‫ا‬ *O$‫ر ا‬2 ‫* أو‬O$‫ ا‬P‫*آ‬
( )
 *O ‫ر‬2 ‫ آ‬x = α #$% ‫  ا‬C f f (α + x ) = f (α − x ) ‫ أو‬f (2α − x ) = f ( x )
 *O P‫ آ *آ‬Ω (α , β ) ‫( ا‬C ) f f (2α − x ) + f ( x ) = 2 β

%‫ رآ‬: ‫"ذ‬#‫ا‬ 0790918876    ‫و  ا ل  أـ ** و   ا‬
(C ) ‫ ـ‬DE‫ ا‬Y $‫ ا‬G ?[E‫( ا‬C ) ‫ ـ‬DE‫ ا‬Y $‫ج ا‬$$‫ا‬
f g f ( x ) W!8 g ( x ) ‫رة‬

. V (0 , k ) B ‫ي‬1‫ب ا‬2%EW8 (C ) ‫( ه رة‬C
f g ) g(x ) = f (x ) + k / k ∈ ℜ
. V (− b ,0 ) B ‫ي‬1‫ب ا‬2%EW8 (C ) ‫( ه رة‬C
f g ) g(x ) = f ( x + b) / b ∈ ℜ

. V (− b , k ) B ‫ي‬1‫ب ا‬2%EW8 (C ) ‫( ه رة‬C
f g ) g(x ) = f ( x + b) + k / b ,k ∈ ℜ
. ‫ر اا‬2 ,‫ إ‬%8 (C ) *-E (C
f g ) g(x ) = − f ( x )
. 5‫*ا‬$‫ر ا‬2 ,‫ إ‬%8 (C ) *-E (C
f g ) g ( x ) = f (− x )
. # ‫ !أ ا‬,‫ إ‬%8 (C ) *-E (C
f g ) g ( x ) = − f (− x )
. x ≤ 0   5‫*ا‬$‫ر ا‬2 ,‫ إ‬%8 (C ) *-E (C ) ‫ و‬x ≥ 0   (C ) , ^ (C
f g f g ) g(x ) = f ( x )
f ( x ) ≤ 0   ‫ر اا‬2 ,‫ إ‬%8 (C ) *-E (C ) ‫ و‬f ( x ) ≥ 0   (C ) , ^ (C
f g f g ) g(x ) = f (x )

lim f ( x ) = ±∞
x→m ∞

f (x)
lim =
x→ m ∞ x

a ∈ ℜ* 0 ±∞

lim [ f ( x ) − ax ] = >? ‫*ع‬:  (C f ) ( )
>? ‫*ع‬:  C f
x →m ∞
( xx′ ) 478 <:= ( yy ′ ) 478 <:=

b∈ℜ ±∞

( )
#$% ‫  ا‬C f >? ‫*ع‬:  (C f )
‫ذو ا د‬ #$% ‫ ا‬478 <:=
#$% ‫ آ‬y = ax + b y = ax ‫ذو ا د‬
; ‫رب‬

+ ‫ا*)(وا ا‬
%‫ رآ‬: ‫"ذ‬#‫ا‬
www.ensdz28.com
0790918876    ‫و  ا ل  أـ ** و   ا‬